Powłoki Walcowe Zamknięć Wodnych - Dąbrowski, R. (Engineering Transactions, 1962)
This is an analysis of the stress in the covering of steel water gates which may be treated as a circular cylindrical shell. After a brief discussion of various theories of such a shell (Sec. 1) further analysis is based on the Donnell differential equation. First, double series are used to solve the problem of a simply supported shell subjected to a hydrostatic pressure or a uniform radial load (Sec. 2). For shells of stronger curvature the convergence of the series is poor. In this case, a boundary value problem is solved, taking into consideration-the coefficient v ≠ 0. Equations for the internal forces are derived (Sec. 3). Next, Sec. 4 contains a discussion, also by using double series, of a clamped shell considered to constitute a portion of a continuous shell. For an orthotropic shell, differential equation is derived corresponding to the Donnell equation (Sec. 5). In Sec. 6 several examples are used to illustrate the distribution of internal forces, above all, in simply supported isotropic shells and the influence of various parameters on their magnitude. Final remarks are devoted to the verification of the stresses taking into consideration the danger of buckling. They are based on the analysis known from textbooks.